Religious diversity and children's literature : strategies and resources - Green, Connie R.; Oldendorf, Sandra Brenneman (Emerald Publishing Limited : Information Age Publishing, Inc., 2011)
This book is an invaluable resource for enabling teachers, religious educators, and families to learn about religious diversity themselves and to teach children about both their own religion as well as the beliefs of others. The traditions featured include indigenous beliefs throughout the world, Native American spirituality, Hinduism, Buddhism, Judaism, Christianity (Orthodoxy, Catholicism and Protestantism), Islam, Sikhism, and other beliefs such as Bahá'í, Unitarian Universalism, Humanism, and Atheism. Each chapter highlights a specific religion or spiritual tradition with a brief discussion about major beliefs, misconceptions, sacred texts, and holy days or celebrations. This summary of each tradition is followed by extensive annotated recommendations for children's and adolescent literature as well as suggested teaching strategies. The recommended literature includes informational books, traditional religious stories, and fiction with religious themes. Teachers, religious educators, and family members will find the literature from these genres to be invaluable tools for bridging the religious experience of the child with that of the global society in which they live.
Keywords: Religious education of children.; Religions -- Juvenile literature -- Book reviews.; Children's literature -- Book reviews.; elektronické knihy; Book reviews.; Education -- Research.; Teaching of a specific subject.; Education.; electronic books